Planning, Monitoring and Evaluation Arrangements in Zambia’s Public Sector: Shifting Sands or a Solid Rock? - Kanyamuna, Vincent; Siamabele, Brivery; Phiri, Million; Mubita, Aurick; Kalonje, Valentine (Advances in Social Sciences Research Journal, 2023)
The paper asks a prime question: Are Zambia’s Planning, Monitoring and Evaluation arrangements Shifting Sands or a Solid Rock? The country, through its policy and legislative instruments has in the recent years articulated and adopted clear frameworks for national planning, budgeting, monitoring and evaluation of public interventions. However, despite these efforts, there still remain a lot of critical questions unanswered. Do the current planning, budgeting, monitoring and evaluation arrangements address Zambia’s development agenda? Are different development plans at national, line ministry, provincial and district level aligned towards a streamlined effort to alleviate the country out of abject poverty? Is there evidence that national annual budgets are directly derived from programmes and activities from various development plans at line ministry, provincial and district levels? Can we track programmes in national development plans (NDPs) within annual budgets? In the literature reviewed, answers to these questions are mixed. While other questions are in the affirmative, many of them have weak evidence. There are strong indications that Zambia’s frameworks for planning, budgeting, monitoring and evaluation would require restructuring to remove redundancies, repetitions and unnecessary bureaucracies. Even when the policies and legislation are clear on what plan needed to be developed and implemented at various levels, in many cases, these remain in draft forever or worse off non-existent. These challenges are more prominent at decentralised levels where plans and M&E practices are weak and fragmented a great deal. Many plans have been prescribed at provincial and district level, yet they are not actualised. They cause staff fatigue on one hand while crowding-out development evidence on the other hand. Therefore, it is recommended that a detailed study is undertaken, one that take the form of a readiness assessment to map out what plans, M&E arrangements and budget frameworks are working well, not working well and reasons why. Such a report will be a good starting point to reform the planning, budgeting, monitoring and evaluation architecture for Zambia. A focused approach will be sound and will lead to a predictable and sustainable development agenda for the country.